VLF Dielectric Response and HF Localized Dielectric Discharge Measurement for Rotating Machine Insulation Assessment - P. Nimsanong; N. Pattanadech (My University, 2020)
This paper represents the very low frequency (VLF) dielectric response and high frequency (HF) localized dielectric discharge measurement for rotating machine insulation assessment. The integral conditions of stator winding insulation, the so-called aging condition, were investigated by the dielectric response measuring technique. The polarization and depolarization currents in the VLF range from 0.0001 to 1 Hz were measured under an external step electric field. The local conditions of stator winding insulation, the so-called weak spot condition, were examined by the partial discharge (PD) measuring technique. The PD pulse currents were detected by a capacitive sensor in a wide-band range, where the bandwidth of the measuring system was set between 30 kHz and 30 MHz. The medium voltage rotating machine rated 6.6 kV and 240 to 2,270 kW under different service conditions, i.e., new stator winding, moisture contamination, dirt contamination as well as thermally and severely aged insulation, was studied. Besides, four case studies on measuring the PD in service rotating machines rated 11–15 kV, 7100 to 211,000 kW as well as the attenuation of the PD pulses were conducted and demonstrated. With several case studies, this paper introduces new dielectric parameters, the so-called charge ratio (QR) and charge difference gradient (QDG), to identify the dielectric mechanism occurring in the stator winding insulation caused by the polarization and conduction processes. It can be concluded that the proposed parameters are a valuable tool for assessing the aging condition. In the case of the PD measurement, it was found that the PD pulse is strongly attenuated in the slot section. This paper also introduces the combination of both the dielectric response and PD measurement results, which can be very useful for assessing a complete insulation condition in the rotating machine. Moreover, the criteria for insulation conditions are suggested in this paper to evaluate the integral and local conditions for the rotating machine insulation. The local discharge in the machine causes electromagnetic waves, which may get released from the non-perfect characteristics of the enclosure. This signal may interfere with the functioning of other nearby electronic devices, especially the communication equipment. Therefore, maintaining the excellent condition of the insulation system by the proposed technique detailed in this paper will support the highly effective operational efficiency of the communication system as well.
Keywords: Insulation system; High voltage insulation and dielectric phenomena